Parental support for young learners' online learning of English in a Chinese primary school. (April 2022) - Tao, Jian; Xu, Yueting
Abstract: Online language learning is challenging to young learners who often need high levels of support from teachers and parents due to their limited skills in self-regulated learning. While technology integration in education is on the rise, there continues to be a lack of research into how young learners can be better supported in online language learning. This qualitative study examines how parents support young learners' online learning of English during the COVID-19 pandemic, based on interviews with 30 parents of students in Grades 1–5 at a Chinese primary school. The study reveals a range of supportive practices: monitoring of learning emerged as the top priority for parents, followed by affective, academic and technology support. Most of these parental support strategies were mediated primarily by the children's grade level and/or parents' socioeconomic background. Parents also sought teachers' help and played bridging roles to enable teacher-student interaction, particularly when they were unable to provide direct help themselves. Based on these findings, we proposed a tripartite model of parental support for young learners' online learning of English to include interactions between parents, young learners, and teachers, which may inform research and practice of young learners' online language learning.